PERBANDINGAN SIKAP SOSIAL SISWA ANTARA TSTS DAN TPS PADA MATA PELAJARAN IPS TERPADU - Ahmad Irvan; Yon Rizal; Pujiati Pujiati (JEE (Jurnal Edukasi Ekobis), 2015)
This study aimed to compare the social attitudes of student by using TSTS and TPSmodel against social attitudes of student in the subject of IPS Terpadu. The method used was the experimental method with a comparative approach. The population was all ofthe seven grade students amounted to 140 students to 54 students that were determined by cluster random sampling. Hypothesis testing was using multivariate analisis of variance and t-test of two independent samples. The result showed that: (1) there are differences in students social attitude using TSTS learning model type and TPS,(2)honest attitude of student in TSTS models is higher than in theTPS model, (3)responsibility attitude of student in TSTSmodelsis lower than in TPS models. (4)the attitude of cooperation of student in TSTSmodels is higher than in the TPSmodel,(5)confident attitude of student in TSTS models higher than in theTPS model and (6)mannered attitude of students in TSTS models is higher than in theTPS model.Penelitian ini bertujuan untuk membandingkan sikap sosial siswa dengan menggunakan model TSTS dan Model TPS terhada sikap sosial siswa pada mata pelajaran IPS Terpadu kelas VII. Metode yang digunakan dalam penelitian ini adalah metode penelitian eksperimen dengan pendekatan komparatif. Populasi dalam penelitian ini seluruh siswa kelas VII yang berjumlah 140 siswa dan sampel berjumlah 54 siswa. Hasil penelitian menunjukan bahwa: Sikap jujur siswa pada model TSTS lebih tinggi dibandingkan pada model TPS, Sikap tanggung jawab siswa pada model TPS lebih tinggi dibandingkan pada model TSTS. Sikap kerjasama siswa pada model TSTS lebih tinggi dibandingkan pada model TPS. Sikap percaya diri siswa pada model TSTS lebih tinggi dibandingkan pada model TPS dan sikap santun siswa pada model TPS lebih tinggi dibandingkan pada model TSTS.Kata kunci: TSTS, TPS, sikap sosial